A novel cellular factor of Nicotiana benthamiana susceptibility to tobamovirus infection - Ershova, Natalia; Kamarova, Kamila; Sheshukova, Ekaterina; Antimonova, Alexandra; Komarova, Tatiana (Frontiers in Plant Science, 2023)
Viral infection, which entails synthesis of viral proteins and active reproduction of the viral genome, effects significant changes in the functions of many intracellular systems in plants Along with these processes, a virus has to suppress cellular defense to create favorable conditions for its successful systemic spread in a plant. The virus exploits various cellular factors of a permissive host modulating its metabolism as well as local and systemic transport of macromolecules and photoassimilates. The Nicotiana benthamiana stress-induced gene encoding Kunitz peptidase inhibitor-like protein (KPILP) has recently been shown to be involved in chloroplast retrograde signaling (CRS) regulation and stimulation of intercellular transport of macromolecules. In this paper we demonstrate the key role of KPILP in the development of tobamovius infection. Systemic infection of N. benthamiana plants with tobacco mosaic virus (TMV) or the closely related crucifer-infecting tobamovirus (crTMV) induces a drastic increase in KPILP mRNA accumulation. KPILP knockdown significantly reduces the efficiency of TMV and crTMV intercellular transport and reproduction. Plants with KPILP silencing become partially resistant to tobamovirus infection. Therefore, KPILP could be regarded as a novel proviral factor in the development of TMV and crTMV infection in N. benthamiana plants. Smith et al., 2011). Virus-induced silencing of ise2 also leads to 351 chloroplast dysfunction, activates retrograde signaling and induces 352 downregulation of such CRS marker genes as GLK1, LHCB 1,2, 353 RBCSIA and others (Ganusova et al., 2020). The relationship 354 between plastids, nuclear gene expression and intercellular traffic 355 regulation forms the basis for a hypothesis that chloroplast signals 356 regulate not only their own metabolism, but also intercellular 357 transport. Therefore, they are key regulators of biological processes 358